[Regional development in the Bajío México from Human Development Index, specially well-being and living conditions] - Aurea Valerdi; Juan Antonio Rodríguez (European Regional Science Association (ERSA), 2013)
As has been said on several opportunities and by many authors (Ferrero 1956, Baran 1961 and Silvestre 1998 cited by Rodríguez 2002 and others), the economic growth measured throughout the GDP is not enough to explain the development and has been unable to reflect by itself the population well-being (social, familiar, individual and psychological). The GDP has also been helpful for economists and leaders in the measure of economic trends' ups and downs and justifying politic decisions. Undoubtedly economic growth means a starting point in the production of goods and services, but quality of life and well-being are also related with other aspects like subjectivity, gender, region, planning, state, etc. Because of the GDP measure's limitations, international organizations has been brought to expose other ways of reflection about development and well-being, like the CEPAL, ONU and PNUD's approaches started in the sixties and seventies and whose latest contribution is the Human Development Index (HDI). The proposal of this contribution is to display some advances about the project named ?Crecimiento económico y desarrollo local en la región centro bajío de México? (Economic growth and development in the México?s central region), made by the academic team ?Transformaciones sociales y dinámicas territoriales? (composed by professors from Division de Ciencias Sociales y Humanidades, Campus León, Universidad de Guanajuato and funded by FORDECYT). This composition shows especially regional data about well-being and living conditions.
Keywords: 330; well-being; living conditions; devepolment; HDI